ChemInform Abstract: Oxidation State 10 Exists. Issue 41 (September 2016) - Yu, Haoyu S.; Truhlar, Donald G.
Abstract: DFT electronic structure calculations indicate the existence of oxidation state 10 in the Td structure of PtO4 2+ .